The effect of repeated transfusions on active cytomegalovirus infection, in the presence of IgM, in patients with thalassemia major in Iran - H Choobineh; Sh Alizadeh; MK Sharifi yazdi; F Vaezzadeh; H Dargahi; AK Pourfatolah (Tehran University of Medical Sciences, 2007)
Background: With due attention to the prevalence of thalassemia in Iran and patients' importunate needs for blood intake, this study aimed to inspect contaminations due to repeated blood transfusion which does not sift in blood donation. One such contamination is cytomegalovirus infection, which is an important pathogen in immunosuppressive patients or receivers of transplanted organs. Methods: This cross sectional study was conducted on 311 thalassemia patients under age of 15 yr who was receiving blood from Hospitals in Tehran and Noorabad Mamasani repeatedly. To determine active infection (presence of IgM antibodies) of cytomegalovirus, ELISA method was used. In addition, 225 healthy people under age of 15 yr were studied as testified group and finally all data were analyzed using SPSS ver. 11.5. Results: 12.9 % of patients were positive from the view point of active infection. Regional separation of patients showed that the patients resided in Tehran are more contaminated to this virus than patients of other cities. Conclusion: The range of cytomegalovirus active infection in thalassemia patients is high. One reason might be the infected blood intake or immunosuppressant (weakness of immune system) in patients, therefore immunity care of these patients and negative serologic blood intake with respect to and also hematic parents (parents with the same blood) are important.